Analisis Pengunaan Bahasa Makian di Kelangan Remaja Desa Wai-Ina Kecamatan Kabau - Boriri, Agus; Samad, Sartika; Umarama, Indra (Peneliti.net, 2024)
This study aims to describe the form of swearing language used by teenagers in Wai-Ina Village, Kabau District and to find out the context of the use of swearing language used by teenagers in Wai-Ina Village, Kabau District. This research method is a qualitative research method. The data collection techniques used are observation techniques, interviews, and documentation studies to obtain information about the swearing language used by teenagers in Wai-Ina Village, Kabau District and the context of its use. The data analysis techniques in this study are in the form of data reduction, data presentation, and drawing conclusions. The results of the study prove that the form of swearing language in the dialect used by teenagers in Wai-Ina Village, Kabau District in their interactions falls into several categories, including 1) categories of animal names, types of professions, types of characteristics, types of objects, and slang. 2) The swear words from the research results are kadai, sundal, basagig, faf nana, batamila, ban baba, panyakbes, basaknau, bajaminto, biadab, anjay, mulu ember, otak udang, anjing. 3) The function of the coarse language used by teenagers in Wai-Ina Village, Kabau District in their social interactions is used as a form of expression to convey the feelings or thoughts of teenagers such as anger, disappointment, admiration, surprise, greetings, and sarcasm.